Pengabdian Kepada Masyarakat Untuk Meningkatkan Partisipasi Masyarakat dan Good governance Tingkat Desa Di Desa Aras Kabu Deli Serdang - Adam Adam; Nina Siti Salmaniah Siregar; Armansyah Matondang; Nina Angelia; Yurial Arief Lubis (Universitas Medan Area, 2021)
Community service activities are one of the activities that aim to assist the government in improving Good Government. Community participation is still very low in implementing the principles of good government. Yet society is a very important part of these principles. Because the role of the community is still very low, community service is held in the form of counseling and socialization about the importance of community participation in improving good government. To realize a civil society, good governance is needed, both at the center and at the local level so that they can work well together so that the goals desired by the community are carried out, and this is not the task of the central government alone but the government under it starting from the village government and local government. that is what we know as the implications of village autonomy. The village community is expected to become a useful community, especially in the process of administering government (at the village level in particular). Because the participation of the village community is a real embodiment of Good governance. This kind of society will be solid and actively participate in determining various government policies. In addition, this kind of society will also carry out an effective supervisory function in the implementation of government administration. If the community is not yet effective in front of the government and there are still many social problems in it such as conflict and group anarchism, it is very unlikely that Good governance can be implemented.